Efficiency of Innovative Technologies in Addressing Environmental Problems in the Agroecosystem of Soya in the Conditions of Southeastern Kazakhstan - Sh. Suleimenova, N.; M. Kuandykova E.M., E.; Zh. Makhamedova, B.; Filipova, M.; ., . (International Journal of Engineering and Technology, 2018)
This article describes the resource-saving innovative technology efficiency in addressing environmental problems of the agroecosystem of soya in the conditions of Southeastern Kazakhstan that have inhibiting effect on the environment at the scale of the cultivated crop. The optimal parameters of the rate of introducing mineral fertilizers in combination with inoculation of soya seeds have been determined, with consideration of their biological features, as one of the methods of resource-saving technology aimed at improving the ecological situation, maintaining stability of the agroecosystem and increasing soya productivity. The rational use of the bioenergy resource and the biological potential of the studied crop have been proven, due to its ability of nitrogen bonding to bond atmospheric nitrogen, thereby reducing the dosage of used nitrogen fertilizers, which contributes to environment protection and resource saving in the agroecosystem. The possibility of replacing the primary dumped tillage with mini-till processing has been found, which provides reliable recovery and preservation of soil fertility. Reducing the mechanical stress during mini-till processing ensures improved water stability of soil aggregates, increases coefficient, and maintains soil structure. The recovered parameters of the agrophysical indicators of soil fertility and reduced total energy costs (fuel consumption) by 21.8-28.4%, as well as the cost of the product with the use of alternative methods technologies in the conditions of the submontane zone of the Southeastern Kazakhstan have been determined.